KAJIAN PERILAKU MASYARAKAT PESISIR YANG MENGAKIBATKAN KERUSAKAN LINGKUNGAN SEKITAR EKOSISTEM MANGROVE DI PANTAI HAMADI KOTA JAYAPURA - Tuhumena, Lolita Constantia; Umbekna, Sara; Rumahorbo, Basa T; Paranoan, Nicea Roona; Mandey, Vera K; Hehanussa, Kedswin G (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background : Environmental damage around the Hamadi coastal mangrove ecosystem, South Jayapura District, Jayapura City, which is caused by many human behavioral factors on the coast, one of which is due to tourism activities that throw away garbage so that it becomes dirty and the natural beauty is damaged. he waste has not been fully addressed effectively if the management is not carried out properly, which then becomes a serious threat to the sustainability of the mangrove ecosystem area near Hamadi Beach which is used as a tourist spot. Therefore, it is necessary to conduct a study of the behavior of the community living around the area and utilizing the area. Method: The researcher used 30 respondents as samples and conducted in June to August 2024 on Hamadi Beach, South Jayapura District, Jayapura City using the data usage technique in this study is Simple Random Sampling, which is carried out randomly from members of the population without considering the level of the population. The data that has been obtained is analyzed using the Likert Scale. Results: Respondents were dominated by men, productive age 36-45 years old, predominantly high school education, fishermen, who had an income Rp 1.000.000 -Rp2.000.000. Socio-economic characteristics describe respondents who live, sell and travel around the area. The characteristics of the respondents were seen from the community's perception of the knowledge of the function of the mangrove ecosystem (3,39) including the category strongly agree, Public Perception of Environmental Conditions for the Growth of Mangrove Ecosystems (3,5) Including the category of strongly agreeing, public perception of the utilization of mangrove ecosystems (3,14) including the category of agree. Conclusion: The development of science about public perception that results in environmental damage to the mangrove ecosystem on Hamadi beach needs to be known in early countermeasures.